How (Not) to Evaluate U.S. Decline and the Emerging Great Power Rivalry - С. Wohlforth (Международная аналитика)
William С. Wohlforth is an American political scientist. Since 2000 he has been a Member of the Government Department’s faculty at Dartmouth College. William С. Wohlforth graduated with a degree in international relations from Beloit College, worked as a legislative aid in the U.S. House of Representatives, and did his graduate work at Yale University, earning an M.A. in international relations and PhD in Political Science. He taught at Princeton and Georgetown. William С. Wohlforth's expertise covers international security and foreign policy. His most recent books are “America Abroad: The United States’ Global Role in the 21st Century” (Oxford, 2018), with co-author Stephen G. Brooks, and “The Oxford Handbook of International Security” (Oxford 2018) co-edited with Alexandra Gheciu. He is currently working on a book on subversion among great powers.